Systematic approach to obtain axillary arterial access for pediatric heart catheterizations - Haddad, Raymond N.; Karmustaji, Fatema; Alloush, Rasha; Al Soufi, Mahmoud; Kasem, Mohamed (Frontiers in Cardiovascular Medicine, 2024)
Background: Axillary arterial access (AAA) in pediatric heart catheterizations is undervalued. Methods: We retrospectively reviewed children with congenital heart diseases (CHDs) who received trans-axillary arterial catheterizations between January 2019 and February 2023. We aimed ultrasound-guided punctures in the proximal two-thirds of axillary arteries with diameters ≥2mm to insert 7cm/4Fr short introducers. We administrated intra-arterial verapamil (1.25mg) and heparin (100UI/kg). We infiltrated per-operatively 2% lignocaine (10mg) for arterial spasms, long sheaths use (≥5Fr), and ≥60 minutes procedures in <3Kg patients. Results: We identified 30 patients (66.7% males) with a median age of 1.1 months (IQR, 0.3-5.4), and a median weight of 3.1 kg (IQR, 2.7-3.7). 5/30 patients had six redo interventions after a median of 3.9 months (IQR, 1.7-5.1). Overall, 27/36 procedures were interventional, including 6 aortic valvuloplasties, 6 balloon angioplasties, and 15 stenting procedures. The median arterial axillary angiographic diameter was 2.6mm (IQR, 2.4-3). Access was right-sided in 23/36 (63.9%) procedures and obtained using 21G/2.5cm bevel needles in 25/36 (69.4%) procedures. No hemodynamical change occurred after introducing spasmolytic drugs. The median fluoroscopy time was 26.1 minutes (IQR, 19.2-34.8). There were two self-resolving arterial dissections, one sub-occlusive arterial thrombosis (resolved with 6 weeks of enoxaparin), and one occlusive arterial thrombosis (resolved with alteplase thrombolysis and 6 weeks of enoxaparin). Median follow-up was 11.7 months (IQR, 8-17.5). Four patients with complex univentricular hearts died from non-procedural causes at a median of 40 days (IQR, 31-161) postoperative. Conclusion: Systematic approach for AAA is the key to success and unlocks the many potentials of trans-axillary pediatric cardiology interventions.